(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
Courts of law have embraced technology at a variant pace, from a minimal adoption of word processing to the extreme end of 100% electronic and web-based without a single paper production. Electronic filing system, case management system, hearing scheduling system, hearing recording system and electronic shorthand system used in courts become important tools that allow cases to be dispensed with in an efficient and timely manner. It enables legal practitioners to work anywhere and anytime. These digital technologies also become enablers for legal information to be accessed online by stakeholders. This paper presents five success factors for successful courtroom technology implementation based on a case study conducted in Malaysia. Data was acquired through collected through qualitative field study consisting of site visits, system demonstrations, interviews, series of observation and documents review. The result shows that the five most important success factors are leadership, change management, financial capital, training and piloting.